VALIDASI METODE ELEKTRODA SELEKTIF ION (ESI) DI PT.PUPUK KALIMANTAN TIMUR UNTUK PENENTUAN KADAR AMMONIA (NH3) DI UDARA AMBIEN - Ristia Asri Fidayana; Teguh Wirawan; Aman Sentosa Panggabean (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2021)
Validation method of ammonia (NH3) determination in ambient air with the ion-selective electrode (ESI) method has been carried out. The purpose of this study is to determine linearity, accuracy, precision, method detection limits, and selectivity. The performance characteristics of the method are determined using standard ammonium chloride solutions. The instrument used to detect ammonia levels is the ion analyzer. The results in the linearity test show an r2 value of 0.9999. Accuracy test results show recovery values in the range of 88.86 to 100.48%. The precision of this method has a value of % RSD smaller than 2/3 CV Horwitz.. The detection limit value of the method was 0.0224 mg/L. The presence of interference ions such as SO2 and NO2 does not affect the measurement of ammonia concentrations. The results of the validation test show that the method used can be used to determine ammonia concentrations in ambient air.